Surface-degenerate semiconductor photocatalysis for efficient water splitting without sacrificial agents via a reticular chemistry approach - Ng, Li Shiuan (2024)
The production of green hydrogen through photocatalytic water splitting is crucial for a sustainable hydrogen economy and chemical manufacturing. However, current approaches suffer from slow hydrogen production (<70 μmol ⋅ gcat -1  ⋅ h-1 ) due to the sluggish four-electrons oxygen evolution reaction (OER) and limited catalyst activity. Herein, we achieve efficient photocatalytic water splitting by exploiting a multifunctional interface between a nano-photocatalyst and metal-organic framework (MOF) layer. The functional interface plays two critical roles: (1) enriching electron density directly on photocatalyst surface to promote catalytic activity, and (2) delocalizing photogenerated holes into MOF to enhance OER. Our photocatalytic ensemble boosts hydrogen evolution by ≈100-fold over pristine photocatalyst and concurrently produces oxygen at ideal stoichiometric ratio, even without using sacrificial agents. Notably, this unique design attains superior hydrogen production (519 μmol ⋅ gcat -1  ⋅ h-1 ) and apparent quantum efficiency up to 13-fold and 8-fold better than emerging photocatalytic designs utilizing hole scavengers. Comprehensive investigations underscore the vital role of the interfacial design in generating high-energy photoelectrons on surface-degenerate photocatalyst to thermodynamically drive hydrogen evolution, while leveraging the nanoporous MOF scaffold as an effective photohole sink to enhance OER. Our interfacial approach creates vast opportunities for designing next-generation, multifunctional photocatalytic ensembles using reticular chemistry with diverse energy and environmental applications.